2005
DOI: 10.1088/0953-8984/17/44/l02
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of La0.825Sr0.175MnO3nanowires

Abstract: Perovskite oxide La 0.825 Sr 0.175 MnO 3 (LSMO) nanowires are synthesized using the anodized alumina oxide template technique and the characterization of the microstructure, magnetic and photoluminescence properties is performed. The as-prepared LSMO nanowires 50 nm in diameter and tens of microns in length exhibit polycrystalline perovskite structure. The magnetic measurement reveals the competition between antiferromagnetic ordering and spin glass state as ground state in the nanowires, which is different fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 21 publications
4
18
0
Order By: Relevance
“…12 The creation of these localized sates can be provoked by the presence of oxygen vacancies. 22,23 The presence of oxygen vacancies in structurally disordered PZT powders is supported by a coexistence of different types of environments for titanium, evidenced by XANES results, given that the reduction of the TiO 6 cluster to TiO 5 cluster may be accompanied by the creation of electron-captured oxygen vacancies. Oxygen vacancies there are not alone, they are bonded to neighbors.…”
Section: Resultsmentioning
confidence: 99%
“…12 The creation of these localized sates can be provoked by the presence of oxygen vacancies. 22,23 The presence of oxygen vacancies in structurally disordered PZT powders is supported by a coexistence of different types of environments for titanium, evidenced by XANES results, given that the reduction of the TiO 6 cluster to TiO 5 cluster may be accompanied by the creation of electron-captured oxygen vacancies. Oxygen vacancies there are not alone, they are bonded to neighbors.…”
Section: Resultsmentioning
confidence: 99%
“…However, several reports in the literature explain the favorable conditions for PL emission in materials presenting a degree of order-disorder. [28][29][30] The authors attributed the radiative decay process to distorted octahedrons, 28 STEs, oxygen vacancies, surface states, 29 and a charge transfer via intrinsic defects inside an oxygen octahedron. 30 As can been seen, there is no general consensus in the literature about why and how radiative decay takes place in perovskitelike structures with a certain degree of disorder.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] However, a few studies have shown the low field MR ͑LFMR͒ effect through artificial or natural grain boundaries, 6 spin-polarized intergrain tunneling, 7 and in trilayer epitaxial tunnel structures 8 but when the temperature increases to room temperature; the LFMR significantly decreases and makes the materials less attractive for the device applications. Due to the difficulty in LSMO nanowire growth, the electrical and magnetotransport studies on one-dimensional LSMO nanowires are not completely explored [9][10][11] and no work has been reported yet on LFMR at room temperature in LSMO nanowires. 12,13 In this work, we have carried out a systematic investigation on magnetotransport properties of electrospun LSMO wires with diameters ranging from 80 to 300 nm.…”
mentioning
confidence: 99%